Asthma-associated genetic variants induce IL33 differential expression through an enhancer-blocking regulatory region - Aneas, Ivy; Decker, Donna C.; Howard, Chanie L.; Sobreira, Débora R.; Sakabe, Noboru J.; Blaine, Kelly M.; Stein, Michelle M.; Hrusch, Cara L.; Montefiori, Lindsey E.; Tena, Juan; Magnaye, Kevin M.; Clay, Selene M.; et al. (Nature communications, 2021)
Genome-wide association studies (GWAS) have implicated the IL33 locus in asthma, but the underlying mechanisms remain unclear. Here, we identify a 5 kb region within the GWAS-defined segment that acts as an enhancer-blocking element in vivo and in vitro. Chromatin conformation capture showed that this 5 kb region loops to the IL33 promoter, potentially regulating its expression. We show that the asthma-associated single nucleotide polymorphism (SNP) rs1888909, located within the 5 kb region, is associated with IL33 gene expression in human airway epithelial cells and IL-33 protein expression in human plasma, potentially through differential binding of OCT-1 (POU2F1) to the asthma-risk allele. Our data demonstrate that asthma-associated variants at the IL33 locus mediate allele-specific regulatory activity and IL33 expression, providing a mechanism through which a regulatory SNP contributes to genetic risk of asthma. Susceptibility to asthma and severity of symptoms are regulated by a number of different genomic regions. Here the authors characterise a 5kb regulatory region and demonstrate genetic and topological regulation of IL33 and association with disease in different human cohorts.